The Importance of Constitutional Awareness for the Exercise of Electoral Rights – Reflections on Guarantees for the Involvement of Social Actors in the Electoral Process - Chmielarz-Grochal, Anna (Teisė, 2023)
In the context of the 2018 amendments to the Electoral Code of the Republic of Poland, which aimed to increase the participation of citizens in elections and ensure the transparency of the electoral procedures, this article analyses the impact of constitutional awareness and the perception of the essence of the mechanisms of government implementation on the active interest of citizens and their involvement in electoral procedures. The author aims to describe the essential aspects of the electoral reform and to determine whether the transformation of the electoral administration model, instead of promoting citizen participation in the electoral process, has reduced their confidence in the credibility and fairness of the electoral procedures. This article was prepared in the framework of the National Science Centre funded research project No. 2017/27/L/HS5/03245 Constitutional Consciousness as a Remedy for the Crisis of Discourse and Democracy Deficit in the European Union (No. DEC-2017/27/L/HS5/03245).